The formation and destruction of stacking fault tetrahedron in fcc metals: A molecular dynamics study. (15th July 2017) - Zhang, Liang; Lu, Cheng; Michal, Guillaume; Deng, Guanyu; Tieu, Kiet
Abstract: Molecular dynamics simulations were conducted to study the formation and destruction of stacking fault tetrahedron (SFT) in fcc metals. The stacking fault energy, the size of vacancy cluster and temperature were found to play a significant role in the formation of a perfect SFT. Also, it was found that the compressive stress can unzip the perfect SFT to a truncated one, and can facilitate the destruction of SFT by transforming the faulted Frank loop to the unfaulted full dislocation loop. We provided the atomic details of how the unfaulting occurs using molecular dynamics method. Graphical abstract: Destruction of stacking fault tetrahedron to the full dislocation loop under compressive loading.